INFLUENCE OF THE COST LEVEL ON ECONOMY OF THE ORGANIZATION AND SAFETY OF ITS FUNCTIONING - Y. Vorontsova; S. Chinyaeva (Вестник университета)
In the article influence of one of the most important indicators of organization activity - product cost - on safety of its functioning is considered. The possibilities of ensuring the economic safety of the organization (ESO) through forming of effective system of monitoring of the allocated ESO indicators are considered. Research of the mechanisms allowing to outline ESO contour through system of interconnected and interdependent indicators of organization activity is provided. The possibility of use for this purpose of the contour of maximum permissible costs (CMPC) is provided. The possibility of forming of strategy of economic safety based on the created price strategy of the organization is considered. In article effective monitoring of costs, expert estimation of coefficient of innovation of the product made by the organization and also control of a large number of the various and difficult indicators influencing their forming as a guarantee of safe management of the organization is also considered.